Pineapple Genome: A Reference for Monocots and CAM Photosynthesis. Issue 11 (November 2016) - Ming, Ray; Wai, Ching Man; Guyot, Romain
Abstract : Pineapple occupies an important phylogenetic position and its reference genome expedites genomic research within the family Bromeliaceae and more widely among monocots. One such research focus is the evolution of crassulacean acid metabolism (CAM) photosynthesis. Acquiring circadian clock cis -regulatory elements in CAM-related genes might be a critical step in the evolution of this form of photosynthesis. Follow-up studies will clarify the processes and evolutionary forces leading to the multiple independent origins of CAM photosynthesis within the family Bromeliaceae and in over 400 genera across 36 families.